Characterization of gel beads used for immobilization of chlorella vulgaris and enhancement its density for lipid production - N. R., Abu Sepian; Nur Hidayah, Mat Yasin; Norazwina, Zainol (IOP Publishing, 2020)
The success of microalgae immobilized in gel beads for lipid production heavily relies on the characteristics of the matrices employed. This study aims to determine cell density and characteristics of immobilized Chlorella vulgaris cells that contributed to the viability of the cells within beads. The new combined matrices with volumetric ratios (Matrices:Microalgae) namely, (1) mixed matrices, SACMCCA (0.3:1) (2) SACA (0.3:1) (3) SACMC (1:1) were proposed in this study and (4) SA (1:1) (sodium alginate, SA; calcium alginate, CA; sodium carboxymethyl cellulose, CMC) as a control experiment. The size of the beads, membrane thickness and chemical compound of these beads were examined. The cell density demonstrated that SACMCCA beads presented the highest value of 1.72 ± 0.5 × 109 cells/mL and lipid yield (30.43 ± 0.30 %) compared to SACA (24.29 ± 0.50 %), SACMC (13.00 ± 0.60 %) and SA (6.71 ± 0.50 %). The characterization had provided important characteristics for a successful entrapment of Chlorella vulgaris. In addition, the combination of single matrices had improved the cell density and lipid production for future applications in the biofuel industry.